Well-being at the heart of policy: lessons from national initiatives around the OECD - Nicola Brandt; Carrie Exton; Lara Fleischer (Forum for a New Economy, 2022)
The COVID-19 crisis is both an enormous challenge and a shock that has prompted many to rethink the status quo. The socio-political effects of the pandemic go far beyond the economy and health care system, touching on many aspects of people's lives and societies' communal fabric, from jobs to education, mental health, gender roles in households, social cohesion and the state of democracy. Some inequalities have deepened - especially for young people, who will continue to feel the consequences of COVID-19 for a long time - and the pandemic has been described as both a wake-up call and dress rehearsal for other crises, including climate change. The fundamental role of public institutions in safeguarding people's well-being has also become apparent. After an initial focus on the emergency response to COVID-19, governments are now developing recovery strategies that will lay the foundations for future well-being. A reflection about what kind of society citizens want to see emerge post-COVID and about what matters most is imperative to "build back better lives". A growing community of practice of governments using a well-being approach to public policy already exists. This brief showcases why well-being approaches have gained traction over the past decade across the OECD, pointing to emerging international consensus on what constitutes "a good life", and how this evidence is increasingly used in innovative ways to inform policy decisions3. Germany has made steps in the past to measure wellbeing more broadly and can benefit from other countries' experience in translating these metrics into practice. This brief is intended to stimulate a discussion on how to do so.
Keywords: 330